DESIGN STUDY OF COLD FORMED STEEL STRUCTURE WITH MATERIAL EXPRESSION ASPECT Case Study: Mosque of Cold Formed Steel Factory Cluster - FITRANTO ADITRA (NIM : 25212041), RAKHMAT
Cold formed steel (CFS) is a steel that shaped under room temperature condition. Differs from hot formed steel (HFS), CFS does not need a lot of energy for combusting. Which means, CFS industry could be done by a smaller factory. Cold formed steel is usually thinner and has a lot more variety of profile. CFS usually also already has coating for rust resisting, so it is more resistance to rust than hot formed steel. Development of CFS as a building structure has gone quite fast, especially for roof structure. However, until now, it is seldom be exposed as aesthetic element. Usually, those structure is hidden because it is too cramped both horizontally and vertically. Structure system with CFS that could be exposed was explored. Hopefully, with that, CFS structure could be an aesthetic element so architect could take role in its development. In this thesis, first, the characteristics of the material and the current development in its structure were reviewed from literatures, then survey and observation of the current development in Indonesia were conducted. From this data, the structure and construction system for mosque were designed. Those design was consulted with civil engineers and CFS factory. Consideration that we used in the design were structural capability, availability of the material, constructability, and visual aspect of the material. The chosen structure was then developed to became a mosque. Rhinoceros and Grasshopper software were used for the design process. From the review, structurally, CFS has weakness in momen and compression force. Beside that, its ductility is lower than hot formed steel. Therefore, the current structure system of CFS is relatively cramped. Roof trusses is organized parallelly and closely. The stud was arrayed, creating a load bearing wall. Connections that mostly used in CFS structure is a screw metal sheet. Connections with weld must consider a lot about the material thickness. Expression that created by the structure with CFS relatively industrial. Meanwhile, for cladding, CFS could create different kind of patterns; horizontal, vertical, embossed or smooth plain. Four option of structure design was produced; trusses, lamella, tension arch and compression arch (vaults). Vaults was selected. Vaults for created from a closely arrayed rib. That structure created a thin skin structure which gave better visual aspect because it is vertically thin. The vaults system also selected because it is possible to redirect the force tangentially to the axis of each steel member. This is a important charateristic of CFS structure which is relatively weak againts momen forces. Moreover, the vaults system was still possible to construct because it was consist of square components that has simpler connections than other shapes. The vault design then was developed into four option. The selected one was the most efisient. From that vault system, shaped was developed. With the help of Rhinoceros and Grasshopper program, parametric design method was applied. The shape was explored to create the proporsional one with the material dimension as the parameters. From the created shape, then it was able to define the folding angle of the one of the compenents. Differs if without parametric, the folding angle was able to define after the shape was decided. With this metode, more shape proportion were able to be explored and more iteration could be done. That system structure created more contemporer mosque. The conventional dome wasnÃ‚Â’t able to be created just by eksposed CFS structure. Tiering vaults were designed to approximately mimic shape of dome. Building like mosque which needs a more varied shape was still hard to designed fully by cold formed steel as structure material than a standarized building like hangar and sport facilities. In the later development, it is need to do research in other case study and a research about constructability and economic efficiency aspects.